Efficacy of the oral mTORC1 inhibitor everolimus in relapsed or refractory indolent lymphoma. Issue 5 (10th March 2017) - Bennani, N. Nora; LaPlant, Betsy R.; Ansell, Stephen M.; Habermann, Thomas. M.; Inwards, David J.; Micallef, Ivana N.; Johnston, Patrick B.; Porrata, Luis F.; Colgan, Joseph P.; Markovic, Svetomir N.; Nowakowski, Grzegorz S.; Macon, William R.; et al.
Abstract: Relapsed indolent lymphoma often becomes refractory to standard chemoimmunotherapy and requires new therapeutic strategies. Targeting the PI3K/mTOR pathway in several types of lymphoma has shown preclinical and clinical efficacy providing the rationale to test this strategy in the treatment of relapsed/refractory indolent lymphomas. We investigated in a phase II open label clinical trial the efficacy and safety of single agent everolimus, an inhibitor of mTORC1, in patients with relapsed/refractory indolent lymphomas. Eligible patients received oral everolimus 10 mg daily on a 28 day‐cycle schedule. The primary endpoint was to evaluate the overall response rate (ORR) and safety of single‐agent everolimus in this patient population. Fifty‐five patients with indolent lymphoma were accrued. The median age was 67 years (range: 33‐85) with a median of five prior therapies (range: 1‐10). The ORR was 35% (19/55; 95% CI: 24‐48%), with complete response unconfirmed in 4% (2/55), and partial response in 31% (17/55). The ORR was 61% (14/23) in the patients with FL. The median time to response was 2.3 months (range: 1.4‐14.1), median duration of response of 11.5 months (95%‐CI: 5.7‐30.4), and a median progression‐free survival of 7.2 months (95%‐CI: 5.5‐12.5). The most common toxicity was hematologic with grades 3‐4 anemia, neutropenia, and thrombocytopenia documented in 15% (8/55), 22% (12/55), and 33% (18/55), respectively. There were no cases of febrile neutropenia, and eight patients discontinued therapy because of adverse events. Everolimus monotherapy is a valid therapeutic option in the relapsed and/or refractory indolent non‐Hodgkin lymphoma patients and is well tolerated.